Emergence of Klebsiella pneumoniae ST11 co-producing NDM-1 and OXA-48 carbapenemases in Greece. (December 2019) - Protonotariou, Efthymia; Meletis, Georgios; Chatzopoulou, Fani; Malousi, Andigoni; Chatzidimitriou, Dimitrios; Skoura, Lemonia
Abstract: Objectives: Klebsiella pneumoniae is a well-known pathogen frequently implicated in serious life-threatening nosocomial infections. Here we present a K. pneumoniae isolate (AHEPA1046) co-harbouring bla NDM-1 and bla OXA-48 isolated from a blood sample of an inpatient in Thessaloniki, Greece. Methods: Whole-genome sequencing (WGS) was performed using an Illumina MiniSeq Sequencing System. Multilocus sequence typing (MLST) was performed using a BLAST-based approach, and antimicrobial resistance genes and plasmid replicons were identified by ResFinder and PlasmidFinder, respectively. The Rapid Annotation using Subsystem Technology (RAST) v.2.0 server was used for genome annotation. Results: WGS analysis revealed the complete resistome of K. pneumoniae AHEPA1046. The strain harboured bla NDM-1 and bla OXA-48 together with 16 additional antimicrobial resistance genes and was resistant to carbapenems, aminoglycosides, quinolones, macrolides, tetracyclines, trimethoprim, fosfomycin and phenicols. Moreover, it was classified as ST11. Conclusion: This is the first report of a K. pneumoniae clinical isolate from Greece co-producing NDM-1 and OXA-48 carbapenemases and is one of a few reported worldwide.